The availability of social skills among kindergarten children in the city of Jableh - حجه, رنا; منال أحمد سلطان ,; بشرى شريبة , (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The aim of this research was to determine the extent of the availability of social skills among kindergarten children in the city of Jableh, and the effect of variables (gender and age) on that. In order to achieve the research objectives, the descriptive approach was used. The research tools were a list of social skills, a pictorial scale to measure the skill (recognizing emotions), and a note card to measure the two skills (good listening and speaking etiquette). The research was applied to a sample of (50) male and female children. The research reached the following results: - The availability of social skills among kindergarten children aged (4-6) years to a moderate degree. - There were no statistically significant differences for social skills according to the gender variable, but they did show statistically significant differences according to the age variable for the skills of listening well and recognizing emotions. This is for the benefit of kindergarten children aged 5-6 years